Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Dengan Purchase Intention Sebagai Variabel Intervening Produk Skintific Pada Marketplace Shopee Di Masyarakat Kota Padang - Nurul Arda; Emil Salim; Della Asmaria Putri (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine and analyze the effect of price and product quality on purchasing decisions through purchase intention as an intervening variable for Skintific products on the Shopee Marketplace among consumers in Padang City. Purchasing decisions for Skintific products on the Shopee Marketplace among consumers in Padang City have not been fully optimized, as reflected by consumers' consideration of price suitability and product quality before making a purchase. In addition, consumers' purchase intention has not been fully established, which consequently affects their purchasing decisions for Skintific products. This study employed a quantitative research method using the Structural Equation Modeling approach analyzed with SmartPLS 3.0 software. The population of this study consisted of consumers in Padang City who had purchased and used Skintific products through the Shopee Marketplace. A total of 100 respondents were selected as the sample using a non-probability sampling technique with a purposive sampling method. The results indicate that price has a significant effect on purchase intention, product quality has a significant effect on purchase intention, price has a significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions, purchase intention has a significant effect on purchasing decisions, and purchase intention is able to mediate the effect of price and product quality on purchasing decisions for Skintific products on the Shopee Marketplace among consumers in Padang City